Amorphous aluminum oxide nanowire material and method for preparing the same

CN121377083BActive Publication Date: 2026-10-30SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511859864.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-10
Publication Date
2026-10-30
Estimated Expiration
2045-12-10

AI Technical Summary

Technical Problem

[0003]本发明所解决的技术问题在于克服现有技术中存在的非晶氧化铝纳米线制备方法复杂且易发生非可控结晶的缺陷,提供一种非晶氧化铝纳米线材料及其制备方法

Benefits of technology

[0027]本发明首次采用氧化物和碘化物的固相反应成功制备得到了具备的纳米线形貌的非晶氧化铝,且本发明提供的制备方法步骤简单、生长周期短、成功率高,获得的非晶氧化铝纳米线数量多、高长径比,形貌均一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377083B_ABST
    Figure CN121377083B_ABST
Patent Text Reader

Abstract

The application discloses an amorphous aluminum oxide nanowire material and a preparation method thereof. The preparation method comprises the following steps: (1) sealing a mixture of ZrO2 powder and AlI3 powder in a reaction tube and then calcining to obtain a precursor aluminum-oxygen-iodine nanowire; and (2) calcining the precursor aluminum-oxygen-iodine nanowire to obtain the amorphous aluminum oxide nanowire material. The preparation method is simple, the reaction source is friendly to the environment, and the preparation method is easy for industrial production. The one-dimensional amorphous aluminum oxide nanowire material prepared by the method has uniform morphology, high length-diameter ratio and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention specifically relates to an amorphous alumina nanowire material and its preparation method. Background Technology

[0002] Alumina nanomaterials are widely used in catalysis, composite materials, and other fields due to their high specific surface area and excellent stability. Among them, one-dimensional nanowire structures have attracted much attention due to their anisotropy and other characteristics. Currently, the preparation technology of alumina nanowires mainly focuses on crystalline materials, such as synthesis through high-temperature vapor deposition, hydrothermal methods combined with high-temperature calcination, or template methods. These methods have significant drawbacks: First, they usually require high-temperature (>1000℃) or high-pressure environments, resulting in high energy consumption and demanding equipment requirements; second, the process flow is complex, often involving toxic precursors or difficult-to-remove catalysts, leading to low product purity; third, the precursors obtained by hydrothermal methods need to undergo high-temperature crystallization treatment, which easily leads to sintering, agglomeration, and morphological destruction of nanowires, resulting in a significant decrease in specific surface area. Compared with crystalline alumina nanowires, amorphous alumina nanowires have a long-range disordered structure, exhibiting unique advantages such as structural uniformity, abundant defects, and high surface energy, showing greater potential in catalysis and interfacial bonding of composite materials. However, existing technologies struggle to directly and efficiently prepare high-purity amorphous alumina nanowires with regular morphology. They generally suffer from complex processes, stringent conditions, and uncontrollable crystallization, severely hindering their application development. Therefore, there is an urgent need to develop a new method for preparing high-purity amorphous alumina nanowires under mild conditions and with a simple process. Summary of the Invention

[0003] The technical problem solved by this invention is to overcome the shortcomings of existing amorphous alumina nanowire preparation methods, which are complex and prone to uncontrollable crystallization, and to provide an amorphous alumina nanowire material and its preparation method. The preparation method of this invention is simple, the reaction source is environmentally friendly, and it is easy to industrialize. The one-dimensional amorphous alumina nanowire material obtained has uniform morphology, a high aspect ratio, and excellent mechanical properties.

[0004] This invention is the first to successfully prepare amorphous alumina nanowires with nanowire morphology using a solid-state reaction of oxides and iodides. First, ZrO2 particles and AlI3 particles are reacted using a solid-state synthesis method to prepare aluminum-oxygen-iodine nanowire precursors. Then, the aluminum-oxygen-iodine nanowires are further annealed in air to transform them into amorphous alumina nanowires.

[0005] The present invention solves the above-mentioned technical problems through the following technical solutions:

[0006] This invention provides a method for preparing amorphous alumina nanowire materials, comprising the following steps:

[0007] (1) The mixture of ZrO2 powder and AlI3 powder was sealed in a reaction tube and then calcined to obtain the precursor aluminum oxy iodine nanowires;

[0008] (2) The precursor aluminum-oxygen-iodine nanowires are calcined to obtain the amorphous alumina nanowire material.

[0009] In step (1), the molar ratio of the ZrO2 powder to the AlI3 powder is preferably no greater than 1, more preferably 0.7-1, for example 0.75, 0.8 or 0.9. When the amount of ZrO2 is too large, the reactants will not react completely, and thus alumina nanowires cannot be obtained.

[0010] In step (1), the preparation method of the mixture of ZrO2 powder and AlI3 powder can be conventional in the art, such as grinding ZrO2 and AlI3 evenly. The grinding is generally carried out under an argon atmosphere.

[0011] In step (1), the reaction tube is preferably a quartz tube.

[0012] In step (1), the calcination is generally carried out in a vacuum environment; before sealing the reaction tube, it is generally necessary to evacuate the reaction tube. After evacuation, the vacuum level inside the reaction tube is preferably less than or equal to 10. -3 Pa. The sealing method can be conventional in the art, such as sealing the tube with a quartz column to achieve a seal.

[0013] In step (1), the calcination can be carried out in a conventional sintering furnace (e.g., a single-zone tube furnace) or a dual-zone tube furnace.

[0014] In step (1), the calcination temperature can be 300-500℃, for example 350℃, 375℃, 400℃ or 450℃; the calcination time can be 48-72h, for example 48h, 50h, 60h, 65h or 70h.

[0015] In step (1), when the calcination is carried out in a dual-temperature zone tube furnace, the high-temperature end temperature of the dual-temperature zone tube furnace is preferably 350-450℃, for example, 380℃, 400℃, 425℃, 430℃, or 450℃; the low-temperature end temperature of the dual-temperature zone tube furnace can be 350-450℃, for example, 350℃, 375℃, or 400℃; the calcination time is preferably 48-80h, for example, 48h, 60h, 70h, or 72h; the rate of heating to the calcination temperature can be 60-300℃ / h, for example, 100℃ / h, 120℃ / h, or 150℃ / h. During the calcination, the end of the reaction tube containing the mixed powder is generally placed in a preset high-temperature zone and held at the preset temperature for a preset time. According to conventional practice in the art, after the calcination is completed, it is generally necessary to allow it to cool naturally to room temperature. According to conventional practice, the high-temperature and low-temperature zones of the dual-temperature tube furnace can each be set with their own calcination temperature and heating rate, with calcination occurring simultaneously in both zones for the same holding time. After calcination, the precursor aluminum-oxygen-iodine nanowires typically grow on the inner wall of the reaction tube.

[0016] In a specific implementation scheme, in step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 450°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 400°C, and the calcination time is 60h.

[0017] In a specific implementation, in step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 425°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 375°C, and the calcination time is 60h.

[0018] In a specific implementation scheme, in step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 450°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 400°C, and the calcination time is 70h.

[0019] In a specific implementation scheme, in step (1), the calcination is carried out in a single-temperature zone tubular furnace, the calcination temperature is 400°C, and the calcination time is 60h.

[0020] In step (1), the diameter of the precursor aluminum-oxygen-iodine nanowire can be 100-300 nm, for example 150 nm, 200 nm or 250 nm; the length of the precursor aluminum-oxygen-iodine nanowire can be 10-150 μm, for example 50 μm, 80 μm, 100 μm or 120 μm.

[0021] In step (2), the calcination is generally carried out in an air atmosphere; the calcination can be carried out in a muffle furnace or a tube furnace. The calcination temperature can be 150-800℃, for example 200℃, 300℃, 350℃, 400℃, 450℃, 500℃ or 600℃; the calcination time can be 0.5-12h, for example 2h, 3h, 4h or 6h; the rate of heating to the calcination temperature can be 60-300℃ / h, for example 100℃ / h, 120℃ / h or 150℃ / h. According to conventional practice in the art, after the calcination is completed, it generally needs to be naturally cooled to room temperature.

[0022] The present invention also provides an amorphous alumina nanowire material prepared by the preparation method described above.

[0023] In this invention, the diameter of the amorphous alumina nanowire can be 50-600 nm, for example 100 nm, 150 nm, 200 nm, 250 nm, 300 nm or 400 nm; the length of the amorphous alumina nanowire can be 10-200 μm, for example 30 μm, 50 μm, 60 μm, 80 μm, 90 μm, 100 μm, 120 μm, 150 μm or 180 μm.

[0024] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0025] The reagents and raw materials used in this invention are all commercially available.

[0026] The positive and progressive effects of this invention are as follows:

[0027] This invention is the first to successfully prepare amorphous alumina with nanowire morphology using a solid-state reaction of oxides and iodides. The preparation method provided by this invention is simple, has a short growth cycle, and a high success rate. The resulting amorphous alumina nanowires are numerous, have a high aspect ratio, and exhibit uniform morphology. Attached Figure Description

[0028] Figure 1 The structure of the quartz tube and the placement of the raw materials in the quartz tube are shown in the embodiments of the present invention.

[0029] Figure 2 An optical photograph of the aluminum-oxygen-iodine nanowires prepared in Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the aluminum-oxygen-iodine nanowires prepared in Example 1;

[0031] Figure 4 The image shows the XRD pattern of the amorphous alumina nanowires prepared in Example 1.

[0032] Figure 5The image shows the Raman diagram of the amorphous alumina nanowires prepared in Example 1.

[0033] Figure 6 This is a scanning electron microscope image of the amorphous alumina nanowires prepared in Example 1;

[0034] Figure 7 XPS image of the aluminum-oxygen-iodine nanowires prepared in Example 1;

[0035] Figure 8 XPS image of the amorphous alumina nanowires prepared in Example 1;

[0036] Figure 9 An optical photograph of the amorphous alumina nanowires prepared in Example 1;

[0037] Figure 10 Thermogravimetric analysis (TGA) diagram of the aluminum-oxygen-iodine nanowires prepared in Example 1;

[0038] Figure 11 A scanning electron microscope image of the tensile testing apparatus described in Example 1;

[0039] Figure 12 The mechanical properties of the amorphous alumina nanowires prepared in Example 1 are shown in the figure.

[0040] Figure 13 This is a scanning electron microscope image of the amorphous alumina nanowires prepared in Example 2. Detailed Implementation

[0041] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0042] Example 1

[0043] (1) High-purity ZrO2 powder (purity of 99.9%) and high-purity AlI3 powder (purity of 99.5%) were mixed in a molar ratio of 3:4 and then ground to obtain a mixed powder. The mixed powder was placed in a quartz tube. The quartz tube containing the mixed powder was evacuated and sealed. It was then placed in a dual-temperature tube furnace. The high-temperature end was heated to 450°C at a rate of 120°C / h, and the low-temperature end was heated to 400°C at a rate of 120°C / h. The temperature was maintained for 60 hours. Then the heating was stopped and the tube was allowed to cool naturally to room temperature. Aluminum-oxygen-iodine nanowires were obtained on the inner wall of the quartz tube.

[0044] (2) The aluminum oxide nanowires were placed in a muffle furnace and heated to 400°C at a rate of 120°C / h and held for 3 hours. Then the heating was stopped and the muffle furnace was allowed to cool naturally to room temperature to obtain high-quality amorphous aluminum oxide nanowires.

[0045] Example 2

[0046] (1) High-purity ZrO2 powder (purity of 99.9%) and high-purity AlI3 powder (purity of 99.5%) were mixed in a molar ratio of 3:4 and ground thoroughly to obtain a mixed powder. The mixed powder was placed in a quartz tube. The quartz tube containing the mixed powder was evacuated and sealed. It was then placed in a dual-temperature tube furnace. The high-temperature end was heated to 425°C at a rate of 120°C / h, and the low-temperature end was heated to 375°C at a rate of 120°C / h. The temperature was maintained for 60 hours. Then the heating was stopped and the tube was allowed to cool naturally to room temperature. Aluminum-oxygen-iodine nanowires were obtained on the inner wall of the quartz tube.

[0047] (2) The aluminum oxide nanowires were placed in a muffle furnace and heated to 400°C at a rate of 120°C / h and held for 3 hours. Then the heating was stopped and the muffle furnace was allowed to cool naturally to room temperature to obtain high-quality amorphous aluminum oxide nanowires.

[0048] Example 3

[0049] (1) High-purity ZrO2 powder (purity of 99.9%) and high-purity AlI3 powder (purity of 99.5%) were mixed in a molar ratio of 3:4 and then ground to obtain a mixed powder. The mixed powder was placed in a quartz tube. The quartz tube containing the mixed powder was evacuated and sealed. It was then placed in a dual-temperature tube furnace. The high-temperature end was heated to 450°C at a rate of 120°C / h, and the low-temperature end was heated to 400°C at a rate of 120°C / h. The temperature was maintained for 70 hours. Then the heating was stopped and the tube was allowed to cool naturally to room temperature. Aluminum-oxygen-iodine nanowires were obtained on the inner wall of the quartz tube.

[0050] (2) The aluminum oxide nanowires were placed in a muffle furnace and heated to 400°C at a rate of 120°C / h and held for 3 hours. Then the heating was stopped and the muffle furnace was allowed to cool naturally to room temperature to obtain high-quality amorphous aluminum oxide nanowires.

[0051] Example 4

[0052] (1) High-purity ZrO2 powder (purity of 99.9%) and high-purity AlI3 powder (purity of 99.5%) are mixed in a molar ratio of 3:4 and ground thoroughly to obtain a mixed powder. The mixed powder is placed in a quartz tube. The quartz tube containing the mixed powder is evacuated and sealed. It is then placed in a tube furnace (a conventional single-temperature zone tube furnace, not a dual-temperature zone furnace). The temperature is raised to 400℃ at a rate of 120℃ / h and held for 60 hours. Then the heating is stopped and the tube is allowed to cool naturally to room temperature. Aluminum-oxygen-iodine nanowires are obtained on the inner wall of the quartz tube.

[0053] (2) The aluminum oxide nanowires were placed in a muffle furnace and heated to 400°C at a rate of 120°C / h and held for 3 hours. Then the heating was stopped and the muffle furnace was allowed to cool naturally to room temperature to obtain high-quality amorphous aluminum oxide nanowires.

[0054] Effect Example

[0055] (1) Morphological and structural characteristics

[0056] Figure 1 This illustrates the structure of the quartz tube in this embodiment of the invention, and the placement of the reactants within the quartz tube during the preparation of amorphous alumina nanowires.

[0057] A physical image of the aluminum-oxygen-iodine nanowires prepared in Example 1 is shown below. Figure 2 As shown, it appears as a regularly arranged array of white nanowires attached to the inner wall of a quartz tube; its SEM image and EDS results are as follows. Figure 3 As shown in the figure, the aluminum-oxygen-iodine nanowires are approximately 100 μm long and 200 nm in diameter. Surface scanning of this region reveals that the nanowires contain Al, O, and I elements. Semi-quantitative analysis indicates that the atomic ratio of Al to O is approximately 1:2. The XPS results are shown below. Figure 7 As shown, the Al 2p spectrum reveals a main peak corresponding to the Al-O bond at 74.8 eV for the prepared aluminum-oxygen-iodine nanowires.

[0058] The XRD pattern of the amorphous alumina nanowires prepared in Example 1 is shown below. Figure 4 As shown, the prepared alumina nanowires are amorphous; their Raman diagram is as follows. Figure 5 As shown, the absence of characteristic peaks in the signal confirms that the alumina nanowires are amorphous; their SEM images and EDS results are as follows. Figure 6 As shown in the figure, the alumina nanowires are approximately 100 μm long and 300 nm in diameter. Surface scanning of this region reveals that the nanowires mainly contain Al and O elements. Semi-quantitative analysis indicates that the atomic ratio of Al to O is approximately 2:3. Its XPS values ​​are as follows: Figure 8 As shown in the Al 2p spectrum, the prepared amorphous alumina nanowire material exhibits a main peak corresponding to the Al-O bond at 74.6 eV; its optical image is shown below. Figure 9 As shown, it appears as white linear clusters.

[0059] The thermogravimetric curve of the aluminum-oxygen-iodine nanowires prepared in Example 1 is shown in Figure 1. Figure 10 As shown in the figure, the mass of the aluminum-oxygen-iodine nanowires gradually decreases during heating and remains stable after 370℃, reflecting the gradual removal of iodine during heating. The SEM images and EDS results of the amorphous alumina nanowires prepared in Example 2 are shown below. Figure 13 As shown in the figure, the alumina nanowires are approximately 100 μm long and 300 nm in diameter. Surface scanning of this region revealed that the nanowires mainly contain Al and O elements. Semi-quantitative analysis showed that the atomic ratio of Al to O was approximately 2:3. Furthermore, the yield of the amorphous alumina nanowires prepared in Example 1 was calculated based on the ratio of actual yield to theoretical yield. The yield results are shown in Table 1. The yield of amorphous alumina nanowires was over 90%, indicating that this preparation strategy has a high success rate.

[0060] Table 1

[0061]

[0062] (2) Mechanical property testing

[0063] The mechanical properties of the final products prepared in the above embodiments were evaluated by in-situ tensile testing using a Picoindenter 85 nanoindenter (Pi-85) integrated in a Quanta 250 FEG scanning electron microscope and a PTP device.

[0064] The final product material prepared in Example 1 was used to fix single amorphous alumina nanowires to the PTP sample region using FIB technology. Its average diameter and initial length were measured based on scanning electron microscopy observations. The cross-sectional area of ​​each cylindrical amorphous alumina nanowire was calculated based on its diameter, while the initial length was defined as the distance between two fixing points. Before testing, a flat probe was positioned to contact the semi-circular end of the amorphous alumina nanowire mounted on the PTP device. In displacement control mode... Tensile tests were performed at a rate until fracture occurred. Force and displacement data were dynamically recorded, and the resulting force-displacement curves included contributions from the PTP device and the amorphous alumina nanowire sample. Therefore, the inherent contribution of the PTP device was subtracted to determine the force applied to the amorphous alumina nanowire sample, and the test results and Figure 11 and Figure 12 As shown:

[0065] Figure 11 The scanning electron microscope images from the mechanical testing device show that the diameter of the tested amorphous alumina nanowires is 300 nm and the length is 2 μm. Figure 12 The test results show that the amorphous alumina nanowires exhibit a high elastic modulus of 0.194 GPa, a strength of 1.03 GPa, and a strain limit of 5.32%.

[0066] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A method for preparing amorphous alumina nanowire materials, characterized in that, It includes the following steps: (1) A mixture of ZrO2 powder and AlI3 powder is sealed in a reaction tube and then calcined to obtain precursor aluminum-oxygen-iodine nanowires; the molar ratio of ZrO2 powder to AlI3 powder is 0.7-1; the calcination is carried out in a dual-temperature zone tube furnace, the high temperature end temperature of the dual-temperature zone tube furnace is 350-450℃, the low temperature end temperature of the dual-temperature zone tube furnace is 350-450℃, and the calcination time is 48-80h; (2) The precursor aluminum-oxygen-iodine nanowires are calcined to obtain the amorphous alumina nanowire material; the calcination temperature is 200-600℃ and the calcination time is 0.5-12h.

2. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (1), the molar ratio of the ZrO2 powder to the AlI3 powder is 0.75, 0.8 or 0.

9.

3. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (1), the reaction tube is a quartz tube.

4. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (1), the reaction tube needs to be evacuated before it is sealed.

5. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (1), the high-temperature end temperature of the dual-temperature zone tubular furnace is 380℃, 400℃, 425℃, 430℃ or 450℃; And / or, in step (1), the low-temperature end temperature of the dual-temperature zone tube furnace is 350°C, 375°C or 400°C; And / or, in step (1), the calcination time is 48h, 60h, 70h or 72h.

6. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 450°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 400°C, and the calcination time is 60h. Alternatively, in step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 425°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 375°C, and the calcination time is 60h. Alternatively, in step (1), the calcination is carried out in a dual-temperature zone tubular furnace, the high-temperature end temperature of the dual-temperature zone tubular furnace is 450°C, the low-temperature end temperature of the dual-temperature zone tubular furnace is 400°C, and the calcination time is 70h.

7. The method for preparing amorphous alumina nanowire material as described in claim 1, characterized in that, In step (2), the calcination is carried out in an air atmosphere; And / or, the calcination temperature is 300°C, 350°C, 400°C, 450°C, 500°C, or 600°C; And / or, the calcination time is 2h, 3h, 4h or 6h.

8. An amorphous alumina nanowire material prepared by any one of claims 1-7.

9. The amorphous alumina nanowire material as described in claim 8, characterized in that, The diameter of the amorphous alumina nanowires is 50-600 nm. And / or, the length of the amorphous alumina nanowires is 10-200 μm.